Sabay tayo a proposed toolkit to promote simultaneous planting among farmers in Sitio St. Joseph, Cabiao, Nueva Ecija - Sarmiento, Allana Marie O.L
Rice is the most important crop in the Philippine agricultural sector playing a significant role in the food security, economy, employment, and overall sustainability It is globally recognized as an essential food and a major source of income for millions of Filipinos. Within the Philippines, Nueva Ecija, recognized as the nation's primary rice-producing province and referred to as the rice granary of the Philippines with 318,284 hectares of land area. Despite its prominent role, the province still faces challenges such as extreme weather events, diseases, and pest infestations, leading to crop damage and low yields. Farmers do not also have access to information and resources that would help them prevent the effects on rice production. An alternative approach is to support them through farmer's association or other collaborative initiatives aimed at improving farmers' well-being by enhancing productivity and increasing income. The study's purpose is to determine the various factors affecting the rice production of farmers in Sitio St. Joseph, Cabiao, Nueva Ecija, with the goal of developing a visual communication intervention in response.